Sovereign Credit Risk Co-movements in the Eurozone: Simple Interdependence or Contagion? - Lena Tonzer; Manuel Buchholz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Since the onset of the eurozone sovereign debt crisis, credit risk spreads in Europe have diverged. Despite this divergence, credit risk comoves strongly within certain country groups such as the eurozone periphery. We seek to answer what the determinants of the observed pattern of credit risk co-movements are and whether and during which periods sovereign debt markets have been subject to contagion. We proceed in three steps. First, we apply dynamic conditional correlations from a multivariate GARCH model to sovereign CDS spreads of 17 countries over the period 2008 to 2012. Second, we separate periods of simple interdependence from contagion. Third, we analyze the determinants behind credit risk co-movements and the role of contagion using regression analysis. Our results reveal a high degree of co-movements in sovereign credit risk, especially for eurozone countries during the sovereign debt crisis. We find strong evidence for both fundamentals and nonfundamentals based contagion. Similarities in economic fundamentals, cross-country linkages in banking and common market sentiment play a significant role.
Keywords: F30; G01; G15; 330